An RFID-based manufacture process control and supply chain management in the semiconductor industry. (1st January 2013) - Tsai, Yung-Shun; Chen, Ruey-Shun; Chen, Yeh-Cheng; Yeh, Chun-Ping
This study proposed an RFID management information system that integrated three common areas in semiconductor testing industry including inventory flows management, location control in warehouse, and handcar localisation. The main core of this research focused on cassette management in semiconductor test industry. The entire management flow enters the warehouse management from a semiconductor manufacturing company to the semiconductor testing company. Based on RFID readers, tags and RFID middleware, label information where located on each cassette will be passed to the backend information system. Through RFID technology characteristic, this system immediately presents the RFID label information for the user to achieve tracing purpose. The research result unified the RFID and the semiconductor testing system to establish a set of immediate information management system. Through the RFID technology and flows integration, this system reduced the standard warehouse working-hour and increased more efficiency in production line. The enterprise saved the more manpower cost, and information transmission was more transparent between customers and suppliers.